Outcome and management of rare high-grade “salivary” adenocarcinoma: the important role of adjuvant (chemo)radiotherapy - Scherl, Claudia; Haderlein, Marlen; Agaimy, Abbas; Mantsopoulos, Konstantinos; Koch, Michael; Traxdorf, Maximilian; Fietkau, Rainer; Grundtner, Philipp; Iro, Heinrich (Strahlentherapie und Onkologie, 2019)
Purpose: To determine survival and management strategies for high-grade adenocarcinoma of salivary glands (ASG). Methods: A retrospective analysis of cases diagnosed between 1998 and 2015 from our single tertiary referral center was performed. Multivariable logistic regression was used to determine factors associated with survival. Results: Thirty-eight cases of high-grade ASG were identified. Most patients were men (68.4%) with a median age of 65.5 years (range 23–84 years). Most tumors were T3 and T4 (65.8%). Regional metastases were common (55.2%), and 42.1% developed distant metastases. The mean follow-up was 60.5 months. All patients received surgery as primary treatment, with 84.2% of patients receiving adjuvant radiation therapy or chemoradiotherapy ([C]RT). Cumulative overall survival was 89.1%, 50.9%, and 20.7% after 1, 5, and 10 years, respectively. Disease-specific survival was 94.4%, 69.8%, and 42.8%, and distant-metastases-free survival (DMFS) was 80.5%, 50.1%, and 40.1% after 1, 5, and 10 years. On multivariable analysis, advanced T status correlated with DMFS (hazard ratio 2.75, 95% CI 0.93–8.16). Postsurgical (C)RT reduced the locoregional recurrence rate by 23.9%, and it improved the locoregional-recurrence-free survival by 39% (p = 0.094). Conclusion: High-grade ASG is considered to have an unfavorable prognosis. Adjuvant (C)RT reduces the rate of locoregional recurrences. Distant metastases are common, and an advanced T stage has increased prognostic value for development of early distant lesions.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Head and neck cancer; Salivary gland cancer; Salivary gland malignancy; Survival salivary gland cancer; Treatment salivary gland cancer